Ponthieva nicolasii (Orchidaceae), una nueva especie para Hidalgo, México - Bertolini, Vincenzo; Archila Morales, Fredy (Gayana Botánica, 2016)
Field studies in the Mezquital Valley of the state of Hidalgo, Mexico, allowed to locate a population of a specie belonging to the genus Ponthieva R.Br. Comparing the specifi es entity to other species of Mexican Ponthieva, we conclude that it is a new taxon, with strong differences between it and the other ones. We report taxonomic diagnosis, descriptor and botanical icon for acceptance.